SAT0420 Increased resistant hypertension in patients with systemic lupus erythematosus: a retrospective cohort study. (12th June 2018) - Gandelman, J.S.; Shuey, M.; Khan, O.; Neal, J.; Dickson, A.; Barnado, A.; Wang, L.; Dupont, W.; Stein, C.M.; Chung, C.P.
Abstract : Background: Resistant hypertension (RHTN) is characterised by blood pressure that remains ≥140/90 mmHg despite concurrent use of 3 antihypertensive drugs. In the general population, RHTN is associated with a 47% increased risk of cardiovascular events. 1 Patients with systemic lupus erythematosus (SLE) have increased cardiovascular risk; however, no research has addressed the incidence, prevalence, or risk factors associated with RHTN in patients with SLE. Objectives: To compare the risk of RHTN in patients with SLE and frequency-matched controls without SLE; to define factors associated with RHTN in patients with SLE. Methods: We used a validated algorithm (94% PPV) to identify patients with SLE from the electronic health records (EHR) at an academic medical centre. 2 We established a control cohort matched by age, race, and sex with a 5:1 control-case ratio. Follow-up began at first ICD9 code for SLE (cases) or first ICD9 code (controls) and continued until RHTN diagnosis or last note. RHTN diagnosis required either the simultaneous use of 3 antihypertensive drugs and a mean blood pressure ≥140/90 mm Hg in the following 6 months, or the use of ≥4 antihypertensive drugs simultaneously. We used logistic regression and Cox proportional hazards (CPH) models to compare risk of RHTN between groups, with CPH performed on incident cases only. Results: We studied 1044 patients with SLE and 5241 controls (median age 42, [31–54] 90% female and 70% Caucasian). Of the total cohort, RHTN developed in 106 SLE patients (10%) and 278 controls (4%). The incidence rate of RHTN was 14.7 cases/1000 person-years in SLE patients compared to 7.4 in controls [HR 1.66, 95% CI, 1.25–2.21] (figure 1). In logistic regression models, RHTN was associated with older age, black race, male gender and end stage renal disease (ESRD). Patients with SLE had a higher risk of RHTN when adjusted for age, sex, race, calendar year, and ESRD [HR 1.53, 1.15–2.05]. In an analysis among SLE patients, RHTN was associated with mortality in an unadjusted model [HR 3.38, 2.20–5.18]. This association remained when age, sex and race were added to the model [HR 2.58, 1.65–4.03], but when ESRD, calendar year and creatinine were included, the association was no longer significant [HR 1.51, 0.91–2.51]. Log rank test: p=0.000391 Conclusions: Patients with SLE have a higher risk of RHTN compared to frequency-matched controls. RHTN is an important comorbiditiy for clinicans to recognise in SLE, as it is associated with a 3.3-fold higher risk of mortality. References: [1] Muntner P, et al. Hypertension2014;64(5):1012–1021. [2] Barnado A, et al. Arthritis Care Res2017;69(5):687–693. Acknowledgements: VUMC's Synthetic Derivative supported by institutional funding and by the CTSA grant ULTR000445 from NCATS/NIH. CTSA awaUL1TR000445 from NCATS, The Rheumatology Research Foundation, Lupus Research Alliance and K-23 award from the NIAMS. Disclosure of Interest: None declared